The Importance of Facilitating Imports for International Trade Flows : Evidence from the Auto Industry - Ereshchenko, Viktoriya (World Bank, Washington, DC, 2021)
Imports are becoming more important than ever in world trade in the face of rapid globalization and the spread of global supply chains. One way to boost imports is through efficient regulations and practices. While the impact of regulatory restrictions is well established for exports, their effect on imports has been studied to a lesser extent across countries. This brief aims to help fill that gap. Focusing on the auto industry, it analyzes the relationship between efficient import procedures and international trade flows in 190 economies. An analysis of the data at the global level suggests that economies where importing auto parts is relatively fast and inexpensive tend to have not only higher imports of auto parts (in terms of volume and value) and a higher ratio of imports of auto parts to total GDP, but also a higher ratio of imports of overall manufactured products to total GDP. Similarly, economies with efficient procedures when importing auto parts tend to have a greater share of automobile exports of total GDP. The Brief does not provide a causal interpretation and more analysis will be needed to understand the direction of the relationships. But given the strong positive association between the efficiency of import procedures and international trade, streamlining import regulations appears to be an important aspect for policy makers to focus on in formulating trade policy.